Mobility Limitations due to Dislocations and Interface Roughness in AlGaN/AlN/GaN Heterostructure. (25th October 2015) - Li, Qun; Zhang, Jingwen; Meng, Li; Chong, Jing; Hou, Xun
Abstract : The dislocations and surface roughness in an AlGaN/AlN/GaN heterostructure were analyzed by transmission electron microscopy (TEM) and atomic force microscopy (AFM), respectively, and the mobility limitation mechanisms in the two-dimensional electron gas (2DEG) were studied using a theoretical model that took into account the most important scattering mechanisms. An exponential correlation function provides a better description of the statistical properties of surface roughness than the Gaussian form and thus is adopted in the theoretical model. The calculated results are in good agreement with Hall data. The quantitative measurements of dislocations and surface roughness allow the evaluation of the relative importance of each extrinsic scattering mechanism.